Sensitivity of turbulent flow around a 3-D building array to urban boundary-layer stability. Issue 193 (October 2019) - Duan, G.; Ngan, K.
Abstract: The mean flow and turbulence within a regular building array are analysed for a wide range of bulk Richardson numbers, Rb, using large-eddy simulation. Time-averaged streamlines in the vertical plane reveal that skimming flow persists for stable and neutral conditions; for unstable conditions, however, updrafts dominate and the counter-rotating vortex pairs in the horizontal plane are displaced towards the leeward wall. The turbulent kinetic energy, magnitude of the turbulent shear stress and mean streamwise flow speed show a sharp transition at Rb = 0 . Quadrant analysis, in particular the fractional stress ratio, indicates that small fluctuations are generated most effectively by neutral flow and large ones by unstable flow. Identical-twin experiments confirm that the effects of stratification are large (pointwise errors in the relative kinetic energy are up to a factor of 10 larger for unstable flow). Knowledge of the flow-regime transition at Rb = 0 is relevant to urban modelling and parameterisation. Highlights: Skimming flow persists for stable stratification. Flow-regime transition occurs at bulk Richardson number Rb = 0. Transition is defined from slope breaks in mean flow and turbulence diagnostics. Ejections dominate under unstable stratification for sufficiently large perturbations. Pointwise errors relative to neutral flow are much larger for unstable stratification.